EFEKTIVITAS METODE PEMBELAJARAN PEER-ASSISTED LEARNING (PAL) TERHADAP PENGETAHUAN TINDAKAN PEMASANGAN INFUS - Syafrinanda, Virginia; Rihiantoro, Tori; Fatonah, Siti (Jurnal Keperawatan Malang, 2025)
Background: One of the basic skills possessed by nursing students is the act of inserting an IV. The act of inserting an IV is one of the basic skills that prospective nurses need to know in meeting patient needs. Efforts to improve student knowledge through the peer assisted learning method which is a method of learning between peers and helping each other to learn. Purpose: to assess the level of student knowledge in the act of inserting an IV through the PAL method Methods: This study uses a pre-experimental research design in the form of a "pretest-posttest with one group design" design by assessing the level of knowledge of inserting an IV before and after the implementation of PAL. before starting the practicum, the lecturer first gives a pre-test then the lecturer demonstrates the practicum to all students. After that the lecturer will determine who will be the peer tutor. after being selected as a peer tutor, they will immediately practice it with their group members. After that the lecturer will give a post-test. Measurement of knowledge with good and poor categories. The population of the study was 98 Level-1 nursing students. The sample of respondents was 46 people. The sampling technique used was purposive sampling. Data analysis using the Wilcoxon statistical test, significance α < 0.05 Result: The level of knowledge of the pre- and post-implementation of PAL infusion installation practical actions obtained good knowledge of 5 people (10.9%) to 36 people (78.3%) and poor knowledge of 41 people (89.1%) to 10 people (21.7%). The results of the Wilcoxon statistical test showed a value of ρ value = 0.002 (ρ value < 0.05) Implication: The application of PAL is very helpful in developing student skills as evidenced by an increase in student knowledge in independent practicum learning